Family, memory and society: reflections on the theatrical experiment O Bosque - Copque, Hayaldo; Santos, Érica Rodrigues dos; Souza, Fernanda Silva; Bomfim, Lorrayne Gabriela da Silva (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2024)
This article analyzes the theatrical experiment O Bosque, composed of three autobiographical solos that explore the possibilities of interweaving the personal and the political in documentary theater. Through the investigation of family memories shared by the actress-creators and a polyphonic theoretical dialogue, with names such as Annie Ernaux, Janaina Leite and bell hooks, this paper aims to comprehend, based on a critical perspective, the social relevance of the family approach based on the diversity of experiences presented.